A novel preparation of Ag-doped TiO2 nanofibers with enhanced stability of photocatalytic activity1. Issue 41 (7th May 2015) - Zhang, Fanli; Cheng, Zhiqiang; Kang, Lijuan; Cui, Liying; Liu, Wei; Xu, Xiaojuan; Hou, Guohui; Yang, Hongjia
<x xml:space="preserve">Abstract</x> A mechanism to form Ag/TiO2 heterostructures by a solvothermal reducing reaction in HMTA solvent is reported.